The role of inflammation in schizophrenia - Müller, Norbert; Weidinger, Elif; Leitner, Bianka; Schwarz, Markus J. (Frontiers in Neuroscience, 2015)
Abstract High levels of pro-inflammatory substances such as cytokines have been described in the blood and cerebrospinal fluid of schizophrenia patients. Animal models of schizophrenia show that under certain conditions an immune disturbance during early life, such as an infection-triggered immune activation, might trigger lifelong increased immune reactivity. A large epidemiological study clearly demonstrated that severe infections and autoimmune disorders are risk factors for schizophrenia. Genetic studies have shown a strong signal for schizophrenia on chromosome 6p22.1, in a region related to the human leucocyte antigen (HLA) system and other immune functions. Another line of evidence demonstrates that chronic (dis)stress is associated with immune activation. The vulnerability-stress-inflammation model of schizophrenia includes the contribution of stress on the basis of increased genetic vulnerability for the pathogenesis